Global and regional levels and trends of child and adolescent morbidity from 2000 to 2016: an analysis of years lost due to disability (YLDs) - David A Ross; Regina Guthold; Emily White Johansson; Colin Douglas Mathers (BMJ Global Health)
Introduction Non-fatal health loss makes a substantial contribution to the total disease burden among children and adolescents. An analysis of these morbidity patterns is essential to plan interventions that improve the health and well-being of children and adolescents. Our objective was to describe current levels and trends in the non-fatal disease burden from 2000 to 2016 among children and adolescents aged 0–19 years.Methods We used years lost due to disability (YLD) estimates in WHO’s Global Health Estimates to describe the non-fatal disease burden from 2000 to 2016 for the age groups 0–27 days, 28 days–11 months, 1–4 years, 5–9 years, 10–14 years and 15–19 years globally and by modified WHO region. To describe causes of YLDs, we used 18 broad cause groups and 54 specific cause categories.Results In 2016, the total number of YLDs globally among those aged 0–19 years was about 130 million, or 51 per 1000 population, ranging from 30 among neonates aged 0–27 days to 67 among older adolescents aged 15–19 years. Global progress since 2000 in reducing the non-fatal disease burden has been limited (53 per 1000 in 2000 for children and adolescents aged 0–19 years). The most important causes of YLDs included iron-deficiency anaemia and skin diseases for both sexes, across age groups and regions. For young children under 5 years of age, congenital anomalies, protein–energy malnutrition and diarrhoeal diseases were important causes of YLDs, while childhood behavioural disorders, asthma, anxiety disorders and depressive disorders were important causes for older children and adolescents. We found important variations between sexes and between regions, particularly among adolescents, that need to be addressed context-specifically.Conclusion The disappointingly slow progress in reducing the global non-fatal disease burden among children and adolescents contrasts starkly with the major reductions in mortality over the first 17 years of this century. More effective action is needed to reduce the non-fatal disease burden among children and adolescents, with interventions tailored for each age group, sex and world region.